4 miti da sfatare sul Reality Capture - Teorema (GEOmedia, 2023)
Teorema Milano, BLK Leica Premium Partner, is a company specialized in the distribution of tools for three-dimensional surveying. The use of the digital representation of 3D models is gaining more and more importance in documenting building construction processes, but also in many other areas. However, as popularity increases, false ideas can also arise. All over the world, reality capture technology developed by Leica Geosystems has given many projects a glimpse into the future. Long gone are the days of recording construction site conditions with a tape measure, spending hours crunching numbers and collecting data by hand, point by point. Reality capture was born out of existing and new innovative technologies fused together to capture digital datasets. This technology has allowed users to implement millions of pieces of information directly into the digitization process in order to create complete 3D models. Reality Capture has turned into a tool for capturing the surrounding world by transforming it into digitally manageable information (data, point clouds) as well as flat and two-dimensional static snapshots. We are now able to capture 3D digital twins, also known as digital realities: replicas of objects, people or places in the physical world created in digital form. Since the creation of the Digital Twins we have evolved towards a Smart Digital Reality that brings autonomy to the digital twin to transform its function and utility. Using technologies such as machine learning and artificial intelligence (AI), we can create systems to reduce, or even eliminate, human intervention and develop dynamic workflows that integrate the right data, in the right place and at the right time. Users can leverage data to empower their applications to self-resolve problems, increasing efficiency, productivity, quality and safety across industries. However, as reality capture technology evolves and becomes more widespread, some false myths have been created that we will see in this article.